Feasibility of a randomized controlled trial of a proprioceptive and tactile vest intervention for children with challenges integrating and processing sensory information - Ann Natasja Nielsen; Karen la Cour; Åse Brandt (BMC, 2022)
Abstract Background Children with challenges integrating and processing sensory information can have difficulties participating in play and learning activities. One way to support participation is to offer sensory stimulation, such as proprioceptive and tactile stimulation provided by wearing a sensory-stimulating vest. The aim of this study was to investigate the feasibility of the key procedures of a planned full-scale randomized controlled trial (RCT) of a proprioceptive and tactile stimulation vest for children aged 6-12 years who have challenges integrating and processing sensory information. The study focused on the feasibility of the recruitment and information processes, the relevance of the study materials, the usefulness of diaries completed by parents, and use of the following outcome measures: Test of Everyday Attention-Children (TEACh), registration of off-task behaviour, and pulse rate. Methods Ten schoolchildren aged 6-12 years (mean 8.4) who had challenges integrating and processing sensory information and sensory-seeking behaviours (based on their Short Sensory Profile scores) participated in the study. Study feasibility was assessed using data from interviews with the participating children, their parents and teachers, and psychologists from the municipal Educational Psychological Counselling Departments. Results Recruitment and introductory materials were found to be relevant and non-problematic, while the outcome measurements, diaries, and pulse measurements did not work well, and the tool for registering off-task behaviours needed to be revised. The results indicated that an outcome measure relating to the children's subjective experiences and closer involvement of teachers in the study could be beneficial. Conclusion The aim of the study was to investigate the feasibility of the planned methodology for a full-scale RCT of a proprioceptive and tactile stimulating vests for children with challenges integrating and processing sensory information. We found that a partial redesign of the study is needed before a full-scale RCT is conducted and that this should include outcome measures on the children's subjective experiences with using the vest.